Pengaruh Keunggulan Relatif, Dukungan Manajemen Puncak, Tekanan Mitra Dagang, Dukungan Penyedia Layanan, dan Inovasi Teknologi Terhadap Adopsi Cloud Accounting pada UMKM di Soloraya - Lia Rahma Ismanabila; Fatchan Achyani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the influence of relative advantage, top management support, trading partner pressure, service provider support, and technological innovation on the adoption of cloud accounting among Micro, Small, and Medium Enterprises (MSMEs) in the Soloraya region. This research employs a quantitative approach with a causal associative design. The data used are primary data collected through questionnaires distributed to 107 respondents using purposive sampling. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software. The results indicate that all independent variables—relative advantage, top management support, trading partner pressure, service provider support, and technological innovation—have a positive and significant effect on the adoption of cloud accounting among MSMEs in Soloraya. This finding suggests that technological, organizational, and environmental factors play a crucial role in driving MSMEs’ digital transformation. The study implies that enhancing digital literacy, strengthening managerial support, and fostering collaboration with business partners and service providers are essential to accelerate the adoption of cloud-based accounting systems. This research is expected to contribute theoretically to the literature on technology adoption and provide practical insights for MSME practitioners, service providers, and policymakers in designing strategies for MSME digitalization in Indonesia.